DESKRIPSI KARAKTERISTIK LINGKUNGAN DAN PERILAKU TERHADAP KEJADIAN MALARIA DI KAMPUNG NEMBUGRESI KABUPATEN JAYAPURA - Madu Pamangin, Lisda Oktavia; Irjayanti, Apriyana (Molucca Medica, 2024)
Jayapura Regency is one of the areas where the malaria rate is still quite high, one of which is Nemburesi Village with an Annual Parasite Incidence (API) above 5.00 (red zone). This research aims to describe the characteristics, environmental conditions and behavior of respondents in Nemburesi Village, Jayapura Regency. The research design used Case Control. The case population was 25, using a total sampling technique and a ratio of cases and controls of 1:1, so that the total was 50 respondents. Data were collected by direct observation and using a questionnaire instrument. Data were analyzed descriptively and presented in cross-tabulation form. The research results showed that among malaria sufferers, 48% of respondents had walls that were not tight, 84% had no ceilings, and 96% had no roofing material. Respondents who suffer from malaria have standing water at 60%, the distance to breeding places that do not meet the requirements is 64%. 96% of respondents who had malaria had a habit outside at night. There is no significant relationship between the external environment and the incidence of malaria (p=0.755). In conclusion, in the variable environmental conditions in the house there are 3 indicators of malaria risk which are more numerous in sufferers, namely; the conditions of the walls are not tight, there is no ceiling, and there is no roofing material. In environmental variables outside the home, there are 2 dominant risk indicators for sufferers, namely; standing water and distance to the breeding place that do not meet the requirements, and in the habit variable there is 1 dominant risk indicator in sufferers, namely; habit of going outside at night.